Cationic Peptides Harboring Antibiotic Capacity are Selective for Leishmania panamensis and Leishmania major (2014)
The fairly recent appearance of Leishmania resistance to currently-used therapy has led to the search for new therapeutic strategies. This work was thus aimed at evaluating the in vitro effect of 18 cationic synthetic antimicrobial peptides for antileishmanial and cytotoxic and haemolytic activity. The viability of murine (J774) and human (U937), peripheral blood monocytes, HeLa and HepG2 cells and L. (V) panamensis and L. (L) major promastigotes was then ascertained using the aforementioned peptides. All antimicrobial peptides were synthesised and each cell and parasite line was treated with different peptide concentrations. Melittin, bombinin, mastoparan 8 (MP-8), MP-X and dermaseptin-S1 reduced human and murine host cells' viability at greater concentrations than pentamidine isethionate, human peripheral blood and U937 monocytes being the most sensitive to peptide action. Melittin had a toxic effect on all the cells evaluated in this study and L. (L) major was more sensitive than L. (V) panamensis to peptide effect. As MP-8, bombinin, dermaseptin-S1 and tracheal antimicrobial peptide (TAP) were active against both parasite species, and tachyplesin 1 and polystes MA selectively so for L. (L) major, they were selected as being promising as they had a >1 selectivity index (SI) and greater than 50 μg/mL haemolytic concentration (HC50), suggesting that they should continue to be studied in in vitro and in vivo infection assays as there have been no previous reports of MP-8, bombinin, TAP and Polystes MA activity regarding L. (V) panamensis and L. (L) major. © 2014 Lozano JM, et al.